2015
DOI: 10.1007/s12649-015-9375-2
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Impacts and Allocation Methods Used in LCA Studies of Vegetable Oil-Based Bio-diesels

Abstract: Life cycle assessment (LCA) is a tool to assess the environmental impacts and resources used during the life cycle of a product, i.e., from raw material acquisition, via production and use phases, to waste management. The methods of development in LCA have been strong, and the paper is aimed at providing a review of recent developments of LCA methods employed in the production of biodiesel from various vegetable sources like Jatropha, palm, soybean, sunflower, canola and rapeseed. The essential features of LCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…Therefore, the second-generation bio-feedstock, such as non-edible oils, used frying oils, animal fats, and greases, has the potential to be more popular in the market. The result showed that the second generation biodiesel from biomass feedstock emits fewer GHG than the first generation diesel from biomass feedstock [144]. In the preparation of biodiesel, the use of catalysts affects the results of LCA [145][146][147].…”
Section: Biodieselmentioning
confidence: 99%
“…Therefore, the second-generation bio-feedstock, such as non-edible oils, used frying oils, animal fats, and greases, has the potential to be more popular in the market. The result showed that the second generation biodiesel from biomass feedstock emits fewer GHG than the first generation diesel from biomass feedstock [144]. In the preparation of biodiesel, the use of catalysts affects the results of LCA [145][146][147].…”
Section: Biodieselmentioning
confidence: 99%
“…The life cycle assessment (LCA) studies for biodiesel showed environmental benefits like moderating the global warming benefits [24,25]. The LCA of palm biodiesel showed a reduction in greenhouse gases (GHG) emissions by 110%.…”
Section: Introductionmentioning
confidence: 99%